Age- and sex-specific relationships between bone mineral density, abdominal fat, and paravertebral muscle - Lei Gao; Ying Liu; Wei Zhang; Yong-li Zheng; Ze-kun Zhang; Xiao-na Zhu; Yan Wang; Jian Zhao (Scientific Reports)
Abstract Bones, muscles and adipose tissue are important endocrine organs, exhibiting intricate interactions. Whether the relationships between bone mineral density (BMD), abdominal fat and paravertebral muscles vary by sex and age remains unclear. The objective of this study was to examine the characteristics of sex- and age-related differences in body composition and to explore the correlations between BMD, abdominal fat, and paravertebral muscles. Lumbar trabecular BMD of L1-L3 vertebrae, visceral fat area (VFA), subcutaneous fat area (SFA), cross-sectional area (CSA) and intermuscular adipose tissue (IMAT) of psoas, and multifidus and erector spinae (MF-ES) muscles measured by quantitative computed tomography (QCT) in 376 subjects were obtained. Fat infiltration fraction (FF) of the muscle was calculated. The body composition was compared after standardization using body mass index (BMI). Partial correlation analysis was utilized to investigate the correlations among components of body composition. The findings showed that females had lower VFA/BMI, CSA of paravertebral muscles/BMI, and higher SFA/BMI, compared to males, but higher FF of muscles only in individuals < 50 years old (P < 0.05). In females over 50 years old, BMD demonstrated a negative correlation with FF of MF-ES (r = − 0.296, P < 0.001). While, VFA, SFA showed positively correlated with FF of MF-ES (r = 0.398, 0.456, both P < 0.001) and FF of psoas (r = 0.352, 0.284, both P < 0.001). With the increase of age, the atrophy of MF-ES tends to increase the IMAT, whereas the atrophy of the psoas muscle tends to reduce CSA. BMD and abdominal fat are associated with paravertebral muscle atrophy and may be potential predictors of paravertebral muscle degeneration in middle-aged and elderly female individuals.